Fatal Delayed Haemolytic Transfusion Reaction and Hyperhaemolysis Syndrome in a Pregnant Woman with Sickle Cell Anaemia - Prof. Madya Dr. Asral Wirda Binti Ahmad Asnawi; Sathar J.; Mohamed R.; Deraman R.; Kumaran S.; Hamid S.S.A.; Zakaria M.Z. (Springer India, 2024)
Clinical manifestations of sickle cell disease (SCD) arise from the tendency of the sickle haemoglobin to polymerize and deform red blood cells into the characteristic sickle shape. Sickle cell crisis is a devastating complication that may occur in patients with SCD. If not managed properly permanent organ damage and even death may be the final outcome. A case of a 32-year-old Nigerian lady, Gravida 1 Para 0 in her first trimester, with SCD who developed signs and symptoms of delayed haemolytic transfusion reaction after receiving packed red cell transfusion is demonstrated. Multiple red cell alloantibodies were detected in the patient’s plasma; anti-Fy a, anti-Jk b and anti-E. The patient miscarriaged and succumbed to complications of hyperhaemolysis with delayed haemolytic transfusion reaction, acute chest syndrome and renal failure. There is an urgent need for mandatory red cell antibody screen and identification especially in high-risk cases. Prevention of alloimmunization by supplying phenotype-specific red cells is also required.